Immigrant court cases: оne hundred years of precedent setting law in Canada - Yahnishchak, Volodymyr (Видавництво Львівської політехніки, 2016)
The paper will outline the links necessary for any researcher to let that researcher write articles and or books that discuss any law that has been tabled by using the precedents in Canada over the past one hundred years.
Keywords: documents; resources; information; Canada; law; court; Court library